Sanitary justice in scarcity - Kottow Miguel (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1999)
Justice in health care and the allocation of scarce medical resources must be analyzed differently in affluent as compared to economically weaker societies. The protective functions of the state must be extended to cover basic needs for those too poor to meet them on their own. Medical needs are a high priority, since poor health hampers the ability to secure other basic needs. The state may operate as either a health care provider or supervisor, guaranteeing that citizens be treated fairly by nongovernmental institutions. Two-tiered systems with a vigorous private health care sector are compatible with the explicit right to health care, provided the private tier operates without directly or indirectly draining public funds.